Kajian KAJIAN SOSIOLOGI SASTRA PADA KUMPULAN CERPEN “RARÉ KUMARA” KARYA I GEDE PUTRA ARIAWAN - I Gusti Ayu Candra Wangi; I Wayan Mandra; Ni Made Ayu Susanthi Pradnya Paramitha (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Short stories are a form of modern Balinese literature that usually tell a fragment of the main character's life, unlike novels that present a complete life story. The short story Raré Kumara by I Gede Putra Ariawan depicts kinship in a family and is based on the reality of human life that is reflected by the author. The stories in this collection of short stories convey messages that are relevant and valuable to society. Based on this background, this study formulates three main problems, namely: (1) what is the intrinsic structure of the Raré Kumara short story collection, (2) what aspects of the sociology of literature are contained in it, and (3) what educational values can be found. The theories used in this study are Teeuw's structuralism theory, Wellek and Warren's sociology of literature theory, and Tarigan's value theory. This study is qualitative-descriptive with data collection techniques in the form of interviews, literature studies, and documentation. The data analysis process includes reduction, discussion, and drawing conclusions. The results of the analysis show that the Raré Kumara short story collection contains important moral messages in community life. Intrinsically, this short story includes elements such as plot, characters, setting, theme, and moral. In terms of literary sociology, a description of the author's social life and background is found. The educational values contained include moral, social, cultural, and religious values.